FAKTOR-FAKTOR YANG MENYEBABKAN KETERLAMBATAN PENYUSUNAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH (APBD) - Helen Aprila Maniagasi; Bonifasia Elitha Bharanti; Ferdinandus Christian (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2016)
The objective of this research was to examine the determinants of delays in Preparations of Regional Revenue and Expenditure. This study was conducted in Sarmi Regency. The population was member of budget board in the House of Representative, budget team from the government agencies and government officials from each work units. There were 60 respondents using a direct survey to collect data. A multiple regressions were employed to empirically test research hypotheses. The research revealed that relation between executive and legislative positively associated with delays in preparations of Regional Revenue and Expenditure. In other words, the better relation between executive and legislative are likely to lower the delays in preparations of Regional Revenue and Expenditure in Sarmi regency. Also, the educational backgrounds positively influence delays in the preparations of Regional Revenue and Expenditure. It means that advancement in educational backgrounds are likely to lower delays in preparations of Regional Revenue and Expenditure in Sarmi regency. Another factor was performance indicators which positively associate with delays in preparations of Regional Revenue and Expenditure. This infers that increase in performance indicators will likely to lower delays in preparations of Regional Revenue and Expenditure in Sarmi regency. Meanwhile, commitment was not supported. Key words: Delays in preparations of Regional Revenue and Expenditure, relation between executive and legislative, educational backgrounds, performance indicators, preparations of Regional Revenue and Expenditure